2014
DOI: 10.1080/00071668.2013.878781
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Iranian field isolatesMycoplasma synoviaeand their differentiation from the live commercial vaccine strain MS-H usingvlhAgene

Abstract: 1. The single-copy domain of the N-terminal region of the vlhA gene of Mycoplasma synoviae was sequenced, analysed and verified and used to type Iranian field isolates of M. synoviae and the MS-H live vaccine strain. In addition, a restriction fragment length polymorphism (RFLP) method was developed to differentiate between field isolates of Iranian and MS-H vaccine strains. 2. All sequences were analysed and aligned; the percentage similarity of the DNA was calculated and dendrograms were constructed. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Analysis of the vlhA gene has been utilized routinely for M. synoviae genotyping (Benčina et al, 2001;Hong et al, 2004;Jeffery et al, 2007;Hammond et al, 2009;Harada et al, 2009;Wetzel et al, 2010;Ogino et al, 2011;ElGazzar et al, 2012;Bayatzadeh et al, 2014). However, the results obtained with vlhA typing are not always consistent with the genogroups determined by conventional typing methods such as restriction fragment length polymorphism (Jeffery et al, 2007).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Analysis of the vlhA gene has been utilized routinely for M. synoviae genotyping (Benčina et al, 2001;Hong et al, 2004;Jeffery et al, 2007;Hammond et al, 2009;Harada et al, 2009;Wetzel et al, 2010;Ogino et al, 2011;ElGazzar et al, 2012;Bayatzadeh et al, 2014). However, the results obtained with vlhA typing are not always consistent with the genogroups determined by conventional typing methods such as restriction fragment length polymorphism (Jeffery et al, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…Typing based on the vlhA sequence has also been proposed for the identification of the vaccine strain MS-H (Jeffery et al, 2007;Harada et al, 2009;Ogino et al, 2011;Bayatzadeh et al, 2014) because the differentiation of this vaccine strain on its temperature-sensitivity characteristics is not always discriminative. The MS-H vaccine strain has a temperature-sensitive (ts+) phenotype, which was obtained by mutagenesis of a temperature-insensitive (ts-) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that MLST based on five genes has a higher discriminatory power than vlhA sequence typing. Moreover, recent studies have shown that vlhA sequence typing can be used successfully for the differentiation between MS-H and M. synoviae field strains in specific geographical areas (Harada et al, 2009;Bayatzadeh et al, 2014), but is not always discriminatory enough (Jeffery et al, 2007;Ogino et al, 2011;Dijkman et al, 2014). Recently, it was shown that the MS-H vaccine strain could be distinguished from all M. synoviae field strains (Shahid et al, 2014) by high resolution melting curve analysis and sequencing of the obg gene making this gene a better target for vaccine strain differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years sequencing of the variable lipoprotein and haemagglutinin (vlh) A gene (Benčina et al, 2001;Hong et al, 2004;Jeffery et al, 2007;Hammond et al, 2009;Harada et al, 2009;Wetzel et al, 2010;El-Gazzar et al, 2012;Dijkman et al, 2014) or restriction fragment length polymorphism of the vlhA gene (Bayatzadeh et al, 2014) had replaced several other molecular typing techniques, like restriction endonuclease analysis of DNA (Morrow et al, 1990b;Ley & Avakian, 1992), pulsed-field gel electrophoresis (Marois et al, 2001;Dufour-Gesbert et al, 2006;Harada et al, 2009), amplified fragment length polymorphism (Feberwee et al, 2005), analysis of the 16S to 23S rRNA intergenic spacer region of M. synoviae (Ramirez et al, 2006(Ramirez et al, , 2011 and random amplified polymorphic DNA analysis (Geary et al, 1994;Marois et al, 2001;Feberwee et al, 2005;Dufour-Gesbert et al, 2006) for typing M. synoviae isolates as these were too labour intensive and therefore costly for large scale application.…”
Section: Introductionmentioning
confidence: 99%